Literature as a Social Mirror and a Cultural Tool For Protest - Torres, Isabel da Conceição Pontes (E- Revista de Estudos Interculturais, 2021)
In a letter to Karl Marx, Friedrich Engels confessed that he learned more from Honoré de Balzac about the French society than from all the books of all the historians, economists and statisticians of the time put together. Literary art has always presenteditself as a social mirror, exposing the reflection of the society in which the writer was inserted, but to what actual extent can Literature reveal and interpret human behavior and society? To what extent can it expose, condemn, and be the engine of its transformation?As Bakhtin's conception argues, the social function of literature as a space for critical reflection, makes, particularly the works that bring the tendency of realistic theory, raise the analysis and weighting of the subject in relation to the society in which they areinserted. This, alongside with the obvious fact that literature is part of the culture of a given society and, therefore, it reveals social patterns that have been considered relevant, and which will help to decipher its mutations, progress and ways of manifesting culture, reveals the value of Literature as an instrument of the social sciences since it allows us to understand what the primary factors of a society are and how they affect it. In this paper I will explain in more detail how literature does then reflect the environment the author lives in and, therefore, its society, to the point where you can identify political, social, economic and several other factors, and use it as a tool to expose and protest many injustices, both if narrating the present or the past, as it is never too late to give a voice to the wronged.